Advanced Photocatalysts: Pinning Single Atom Co-Catalysts on Titania Nanotubes - Zhou, Xin; Hwang, Imgon; Tomanec, Ondrej; Fehn, Dominik; Mazare, Anca Valentina; Zboril, Radek; Meyer, Karsten; Schmuki, Patrik (Advanced Functional Materials, 2021)
Single atom (SA) catalysis, over the last 10 years, has become a forefront in heterogeneous catalysis, electrocatalysis, and most recently also in photocatalysis. Most crucial when engineering a SA catalyst/support system is the creation of defined anchoring points on the support surface to stabilize reactive SA sites. Here, a so far unexplored but evidently very effective approach to trap and stabilize SAs on a broadly used photocatalyst platform is introduced. In self-organized anodic TiO2 nanotubes, a high degree of stress is incorporated in the amorphous oxide during nanotube growth. During crystallization (by thermal annealing), this leads to a high density of Ti3+-Ov surface defects that are hardly present in other common titania nanostructures (as nanoparticles). These defects are highly effective for SA iridium trapping. Thus a SA-Ir photocatalyst with a higher photocatalytic activity than for any classic co-catalyst arrangement on the semiconductive substrate is obtained. Hence, a tool for SA trapping on titania-based back-contacted platforms is provided for wide application in electrochemistry and photoelectrochemistry. Moreover, it is shown that stably trapped SAs provide virtually all photocatalytic reactivity, with turnover frequencies in the order of 4 × 106 h−1 in spite of representing only a small fraction of the initially loaded SAs.
CRIS-Team Scopus Importer:2021-06-04
Keywords: dark deposition; hydrogen generation; photocatalysis; single atom iridium; single-atom catalysis; TiO

Critical factors for photoelectrochemical and photocatalytic H-2 evolution from gray anatase (001) nanosheets - Qin, Shanshan; Denisov, Nikita; Zhou, Xin; Zdražil, Lukáš; Fehn, Dominik; Hwang, Imgon; Bruns, Mark; Kim, Hyesung; Meyer, Karsten; Schmuki, Patrik (JPhys Energy, 2022)
In recent years, the defect engineering of titania via reduction treatments has shown a high potential for enabling efficient and co-catalyst-free photocatalytic H-2 generation from methanol/water solutions. However, defect engineering simultaneously alters several properties of TiO2. Here, we use pristine (white) and hydrogenated (gray) anatase nanosheets with dominant (001) facets. By comparing electrical conductivity, photocurrent spectra, transient photocurrent response, and photocatalytic H-2 evolution, we show that the increased conductivity or broad visible light absorption of gray titania is not responsible for its increased activity. Instead, the true bottleneck is the hole transfer rate that is significantly accelerated while using gray instead of white modification. Moreover, the hole transfer reaction causes the accumulation of the reaction products in pure water, hindering the photocatalytic H-2 evolution over time. These combined factors explain the superior performance of gray titania over white titania in photoelectrochemical or photocatalytic water splitting.
CRIS-Team WoS Importer:2022-10-07

Efficient, stable, and fully printed carbon-electrode perovskite solar cells enabled by hole-transporting bilayers - Du, Tian; Qiu, Shudi; Zhou, Xin; Le Corre, Vincent Marc; Wu, Mingjian; Dong, Lirong; Peng, Zijian; Zhao, Yicheng; Jang, Dongju; Spiecker, Erdmann; Brabec, Christoph; Egelhaaf, Hans-Joachim (Joule, 2023)
Printable planar carbon electrodes emerge as a promising replacement for thermally evaporated metals as the rear contact for perovskite solar cells (PSCs). However, the power conversion efficiencies (PCEs) of the state-of-the-art carbon-electrode PSC (c-PSC) noticeably lag behind their metal-electrode counterparts. Here, we propose a hole-transporting bilayer (HTbL) configuration to improve the fill factor and the open-circuit voltage of c-PSCs simultaneously. The HTbL is prepared by sequentially blade coating two organic semiconductors between perovskite and carbon, with the outer HTL enhancing hole extraction to carbon, while the inner HTL mitigates perovskite surface recombination. Consequently, our fully printed c-PSCs with HTbL outperform those with single HTL, and a stabilized champion PCE of 19.2% is achieved compared with that of 17.3%. Our prototype c-PSC stably operates during 1 sun, 65°C aging test (ISOS-L-2I) for 2,500 h showing negligible PCE drop, validating its potential as a highly cost-effective photovoltaic technology.
CRIS-Team Scopus Importer:2023-08-18
Keywords: bilayer; carbon electrode; fully printed perovskite solar cells; hole transporting; stability

Overcoming Temperature-Induced Degradation of Silver Nanowire Electrodes by an Ag@SnOx Core-Shell Approach - Kalancha, Violetta; These, Albert; Vogl, Lilian; Levchuk, Ievgen; Zhou, Xin; Barr, Maissa; Bruns, Mark; Bachmann, Julien; Virtanen, Sannakaisa; Spiecker, Erdmann; Osvet, Andres; Brabec, Christoph; et al. (Advanced Electronic Materials, 2022)
Transparent electrodes consisting of silver nanowires (Ag NWs) are a solution-processed alternative to commonly used indium tin oxide electrodes. Here, Ag NW electrodes protected by a tin oxide (SnOx) are explored and unprecedented thermal stability is found. While unprotected Ag NW electrodes fail at 250 degrees C, the SnOx Ag NW electrodes remain stable for 40 h at 250 degrees C and withstand high temperatures up to 500 degrees C for short times. First, an optimized method of synthesis that provides uniform Ag NWs with high reproducibility is used. Afterward, a SnOx shell is formed in a wet chemical reaction. Fabrication of highly conductive electrodes requires thermal annealing at 300 degrees C for 5 min under ambient atmosphere. Electrodes with a sheet resistance as low as 20 ohm sq(-1) and visible transmittance of 84% are demonstrated. It is shown that a approximate to 2 nm thick SnOx shell effectively protects the Ag NWs in a temperature range between 200 and 500 degrees C, whereas unprotected Ag NWs suddenly fail at temperatures beyond 200 degrees C. It is strongly anticipated that these improvements in the stability of Ag NWs open a large field of further investigations and applications.
CRIS-Team WoS Importer:2022-02-11

Photocatalytic Synthesis of Oxidized Graphite Enabled by Grey TiO2 and Direct Formation of a Visible-Light-Active Titania/Graphene Oxide Nanocomposite - Nasir, Amara; Mazare, Anca Valentina; Zhou, Xin; Qin, Shanshan; Denisov, Nikita; Zdrazil, Lukas; Kment, Stepan; Zboril, Radek; Yasin, Tariq; Schmuki, Patrik (Chemphotochem, 2022)
Herein we report a one-step, low cost, photocatalytic method for the synthesis of graphene oxide (GO) from commercial graphite using grey TiO2 as a photocatalyst. GO formation is achieved by UV-illumination of a slurry of well-dispersed grey TiO2 and commercial graphite. Light-induced valence-band holes from grey TiO2 then lead to an oxidation and exfoliation of graphite, resulting in the formation of visible-light-active GO. An optimal level of graphite oxidation can be established by controlling the UV illumination time. Moreover, the resulting GO-decorated TiO2 is directly active as a visible-light-active photocatalyst that can, for example, be used for pollution degradation.
CRIS-Team Scopus Importer:2022-04-15
Keywords: graphene oxide; graphite; grey TiO; methylene-blue degradation; UV illumination

Photocurrent conversion efficiency of TiO2 nanotube photoanodes in dependence of illumination intensity - Denisov, Nikita; Zhou, Xin; Cha, Gi; Schmuki, Patrik (Electrochimica Acta, 2021)
In the present work, we investigate the photoresponse of TiO2 nanotube photoanodes as a function of the illumination intensity and compare it to compact anodic TiO2 layers. While for the compact layers, in line with expectations, the IPCE is virtually independent of the light intensity, we find for the nanotube morphology a significant increase in the magnitude of the IPCE with lowering the illumination intensity. Moreover, for low light intensities a noticeable change in the IPCE spectra, a substantial slowdown of the transient photocurrent kinetics, an increase of the charge transport time constants, and an anodic shift of the optical flat-band potential is observed. We attribute the sensitivity of the IPCE and other photoresponse effects mainly to a hole accumulation and trapping caused by higher illumination intensities – this effect is particularly strong due to the geometry of the tubes. The observed effects have significant implications for the interpretation and comparability of the TiO2 NT photocurrent data.
CRIS-Team Scopus Importer:2021-03-19
Keywords: IMPS; IPCE; Mott-Schottky analysis; Photoelectrochemistry; TiO2 nanotubes

Photoelectrochemical performance of TiO2 photoanodes: Nanotube versus nanoflake electrodes - Zhou, Xin; Denisov, Nikita; Cha, Gi; Hwang, Imgon; Schmuki, Patrik (Electrochemistry Communications, 2021)
In the present work, we compare the photoresponse of vertically erected (VE) single crystal anatase layers with that of widely used TiO2 nanotube layers. These VE-anatase layers were grown hydrothermally, directly on fluorine-doped tin oxide (FTO) glass, and consist of an array of anatase single crystal flakes with preferred (0 0 1) facets. As formed, these single crystal layers are fluorine terminated – this termination can be removed by a thermal treatment in air. We compare the photocurrent magnitude and photocurrent transients using intensity-modulated photocurrent spectroscopy (IMPS). We find that the “de-fluorinated” VE-anatase layers show significantly higher photocurrents than the comparable nanotube layers. This high efficiency of the VE-anatase layers is due to the electron transport being 100 times faster in these single crystal electrodes, provided that the blocking fluorine termination is removed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: IMPS; IPCE; Photocurrent transients; TiO; VE-anatase layers

Pt Single Atom Deposition by Direct Current Sputtering in the Gas-Scattering Regime—A Simple Approach to Controlled Single Atom Loading - Zhou, Xin; Kim, Ji Hyeon; Kim, Hyesung; Zahra, Sani; Schmuki, Patrik (Chemsuschem, 2025)
Supported single atoms represent a new frontier in many catalytic fields, and noble metal single atoms in particular have been reported to be a highly effective cocatalyst in photocatalysis or electrocatalysis. Herein, it is described that direct current sputtering of Pt, when operated under plain gas-scattering conditions, can be leveraged for single atom deposition on various substrates (herein TiO2 and graphene are used as examples). The approach allows a uniform single atom deposition with a high level of control over single atom density and loading amount on both surfaces. Such Pt single atoms on TiO2 can be used directly (without further treatments) as cocatalysts for photocatalytic H2 generation. Remarkably, single atom loading and H2 generation activity correlate linearly over a wide range of Pt loading (0.16–1.41 at%). The findings not only open a new avenue for the synthesis and use of single atoms in photocatalysis but also highlight the use of gas-phase scattering as a simple, scalable, and versatile approach for single-atom catalyst fabrication.
CRIS-Team Scopus Importer:2025-05-23
Keywords: hydrogen generation; photocatalysis; platinum; single-atom catalysis; sputter deposition

Pt Single Atoms Loaded on Thin-Layer TiO2 Electrodes: Electrochemical and Photocatalytic Features - Zhou, Xin; Wang, Yue; Denisov, Nikita; Kim, Hyesung; Kim, Ji Hyeon; Will, Johannes; Spiecker, Erdmann; Vaskevich, Alexander; Schmuki, Patrik (Small, 2024)
Recently, the use of Pt in the form of single atoms (SA) has attracted considerable attention to promote the cathodic hydrogen production reaction from water in electrochemical or photocatalytic settings. First, produce suitable electrodes by Pt SA deposition on Direct current (DC)-sputter deposited titania (TiO2) layers on graphene—these electrodes allow to characterization of the electrochemical properties of Pt single atoms and their investigation in high-resolution HAADF-STEM. For Pt SAs loaded on TiO2, electrochemical H2 evolution shows only a very small overpotential. Concurrent with the onset of H2 evolution, agglomeration of the Pt SAs to clusters or nanoparticles (NPs) occurs. Potential cycling can be used to control SA agglomeration to variable-size NPs. The electrochemical activity of the electrode is directly related to the SA surface density (up to reaching the activity level of a plain Pt sheet). In contrast, for photocatalytic H2 generation already a minimum SA density is sufficient to reach control by photogenerated charge carriers. In electrochemical and photocatalytic approaches a typical TOF of ≈100–150 H2 molecules per second per site can be reached. Overall, the work illustrates a straightforward approach for reliable electrochemical and photoelectrochemical investigations of SAs and discusses the extraction of critical electrochemical factors of Pt SAs on titania electrodes.
CRIS-Team Scopus Importer:2024-08-23
Keywords: anatase thin film electrode; electrocatalytic hydrogen evolution; graphene; photocatalytic hydrogen evolution; Pt Single atom

Spontaneous Dewetting of Au-Thin Layers on Oxide- and Fluorine-Terminated Single Crystalline Anatase and Efficient Use in Photocatalytic H2 Production - Zhou, Xin; Wu, Siming; Schmuki, Patrik (Small, 2023)
In the present work, the spontaneous dewetting of thin Au layers on single crystalline anatase nanosheets into narrow-disperse Au nanoparticles is investigated. Patterns of the Au particles can be formed on the main facets of anatase that provide a high co-catalytic activity for photocatalytic generation of H2. Dewetting is distinctly influenced by the respective facets (001) and (101), the deposit thickness, and secondary thermal dewetting, but most strongly by the surface termination of the nanosheets. Fluoride termination not only leads to an enhanced Au-phobic behavior but strongly affects the co-catalytic activity for photocatalytic generation of H2. While fluoride termination with or without Au decoration is detrimental for hole transfer, the interplay of the Au co-catalyst and surface fluoride yields highly beneficial effect for electron transfer. This results in a three-times higher photocatalytic H2 production for the F-terminated surface. The findings suggest that dewetting of Au on surface fluorinated TiO2 is an effective way to modulate surface dewetting and achieve a strongly enhanced photocatalytic activity.
CRIS-Team Scopus Importer:2023-07-07
Keywords: dewetting; photocatalytic H; single crystalline anatase TiO; surface fluorination